Analisis Model Altman Z”-Score Sebagai Prediksi Kebangkrutan - Rivka Izzati Nisa; Chasan Azari; Winarto (Journal Of Accounting and Business, 2024)
The retail business is a great opportunity for Indonesia because some people earn income from selling retail goods, but in recent years retail companies in Indonesia have experienced a slowdown, impacting many large and well-known retail outlets in Indonesia that have begun to stop their business for various reasons. Increasingly sophisticated technological developments such as the emergence of e-commerce that is more attractive to buyers because of the ease of transacting at a much more affordable price is one of the reasons. This study aims to analyze the prediction of potential bankruptcy in retail subsector companies on the Indonesia Stock Exchange for the 2018-2021 period by applying the Altman Z"-Score model. Sampling using purposive sampling techniques with samples of five retail companies listed on the IDX for the 2018-2021 period with a total of The sample is 5 companies, namely GLOB, HERO, MKN, MPPA and TRIO. This research uses a type of descriptive research using quantitative methods. Based on the results of research the Altman Z "-Score method categorizes companies in three categories, namely not bankrupt (safe zone) with a cut off value of Z" > 2.60; prone (gray zone) with a cut off value of 1.10 < Z'' < 2.60 and bankrupt (distress zone) with a cut off value of Z" < 1.10, which means that the company in the HERO category is in the gray zone or it could be said that the company is in a vulnerable condition. This is indicated by a Z"-Score value of 1.10 < Z "< 2.60. MKNT is in the distress zone position, the company shows a decreasing and negative Z"-Score value, namely Z"-Score < 1.10, which means the company is in a state of bankruptcy, the Z" value. -The score is decreasing and negative, namely the Z"-Score value < 1.10 which means the company is in a state of bankruptcy. Based on these results, the Z"-Score value is < 1.10 which means the company is in a bankrupt position. So suggestions for a) company managers who have a Z"-Score < 1.10 are expected to optimize the e-commerce platform as an alternative to cut working capital costs, land rental costs and cut other escalating costs and for investors it can be a consideration in taking investment decisions to minimize losses by utilizing Altman Z"-Score analysis.